2010
DOI: 10.1159/000322952
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Is an Independent Predictor of All-Cause Mortality in Hemodialysis Patients

Abstract: Background: Dietary n–3 polyunsaturated fatty acids (PUFAs), docosahexaenoic acid (DHA) and eicosapentaenoic acid have been shown to reduce cardiovascular mortality. Patients on hemodialysis (HD) have a very high mortality from cardiovascular disease. Fish consumption reduces all-cause mortality in patients on HD. Moreover, n–3 PUFAs, especially DHA levels in red blood cells (RBCs), are associated with arteriosclerosis in patients on HD. The aim of this study was to determine whether DHA levels in RBCs predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
5
17
0
6
Order By: Relevance
“…In the previous 5‐year cohort study, we found that DHA in RBCs could be an independent predictor of all‐cause mortality in HD patients . In the present study, although the duration was extended to 10 years, we still observed a similar inverse association.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the previous 5‐year cohort study, we found that DHA in RBCs could be an independent predictor of all‐cause mortality in HD patients . In the present study, although the duration was extended to 10 years, we still observed a similar inverse association.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, although the duration was extended to 10 years, we still observed a similar inverse association. There was no correlation between other n‐3 PUFAs such as EPA and the risk of all‐cause mortality, which was also the case in the previous study . It is of great interest that DHA but not EPA was associated with all‐cause mortality.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Hamazaki reported that HD patients with higher levels of DHA in their red blood cells showed a better prognosis than those with lower levels (20). It remains to be determined which of the PUFAs is more effective for reducing mortality in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found a trend between a erythrocyte omega 3 index levels and survival amongst HD patients; however, the fact that this did not reach statistical significance may be ascribed to an insufficient cohort size to achieve adequate statistical power [180]. Recent longitudinal observational cohort studies have found that the DHA content of erythrocyte plasma membranes is able to independently predict mortality outcomes in HD patients [181,182]. Other studies investigating the fatty acid profile of the serum and mortality in HD patients may be predicted by serum DHA levels [183] or the ratio between n -3 and n -6 [184].…”
Section: Omega-3 Polyunsaturated Fatty Acids (N-3 Pufas)mentioning
confidence: 99%